Hypertonic Saline Nasal Rinse Intervention: Immunomodulatory Effects in Dairy Workers - Grant Erlandson; Sheryl Magzamen; Julia L. Sharp; James Seidel; Jill A. Poole; Mary Bradford; Joshua W. Schaeffer (Journal of Agromedicine, 2025)

Supergene formation of sulfur-rich, tochilinite-bearing serpentinites in the Oman ophiolite - James Andrew Leong; Juan Carlos de Obeso; Thomas Sharp; Everett Shock; Peter Kelemen (Lithos, 2024)

Systematic review and meta-analysis on the impact of COVID-19 related restrictions on air quality in low- and middle-income countries - Annalan M.D. Navaratnam; Harry Williams; Stephen J. Sharp; James Woodcock; Haneen Khreis (Science of The Total Environment, 2024)

Transitional dynamics from mercury to cyanide-based processing in artisanal and small-scale gold mining: Social, economic, geochemical, and environmental considerations - Aaron Malone; Linda Figueroa; Weishi Wang; Nicole M. Smith; James F. Ranville; David C. Vuono; Francisco D. Alejo Zapata; Lino Morales Paredes; Jonathan O. Sharp; Christopher Bellona (Science of The Total Environment, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Heavy metal removal by the photosynthetic microbial biomat found within shallow unit process open water constructed wetlands - Zhaoxun Yang; Sarah M. Acker; Adam R. Brady; Armando Arenazas Rodríguez; Lino Morales Paredes; Juana Ticona; Giuliana Romero Mariscal; Gary F. Vanzin; James F. Ranville; Jonathan O. Sharp (Science of The Total Environment, 2023)

What's the crux? Falcon nesting closures and rock climbing constraints at Harpers Ferry National Historical Park - Michala L. Hendrick; Chris A.B. Zajchowski; Jessica P. Fefer; Ryan L. Sharp; Chandler Berry; James N. Maples; Eddie L. Hill (Journal of Outdoor Recreation and Tourism, 2023)

The blowfly Chrysomya latifrons inhabits fragmented rainforests, but shows no population structure - Nathan J. Butterworth; James F. Wallman; Nikolas P. Johnston; Blake M. Dawson; Joshua Sharp-Heward; Angela McGaughran (Oecologia, 2023)
Climate change and deforestation are causing rainforests to become increasingly fragmented, placing them at heightened risk of biodiversity loss. Invertebrates constitute the greatest proportion of this biodiversity, yet we lack basic knowledge of their population structure and ecology. There is a compelling need to develop our understanding of the population dynamics of a wide range of rainforest invertebrates so that we can begin to understand how rainforest fragments are connected, and how they will cope with future habitat fragmentation and climate change. Blowflies are an ideal candidate for such research because they are widespread, abundant, and can be easily collected within rainforests. We genotyped 188 blowflies ( Chrysomya latifrons ) from 15 isolated rainforests and found high levels of gene flow, a lack of genetic structure between rainforests, and low genetic diversity – suggesting the presence of a single large genetically depauperate population. This highlights that: (1) the blowfly Ch. latifrons inhabits a ~ 1000 km stretch of Australian rainforests, where it plays an important role as a nutrient recycler; (2) strongly dispersing flies can migrate between and connect isolated rainforests, likely carrying pollen, parasites, phoronts, and pathogens along with them; and (3) widely dispersing and abundant insects can nevertheless be genetically depauperate. There is an urgent need to better understand the relationships between habitat fragmentation, genetic diversity, and adaptive potential–especially for poorly dispersing rainforest-restricted insects, as many of these may be particularly fragmented and at highest risk of local extinction.

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

The distribution, ecology and predicted habitat use of the Critically Endangered angelshark ( Squatina squatina ) in coastal waters of Wales and the central Irish Sea - Joanna Barker; Jake Davies; Monika Goralczyk; Surshti Patel; John O'Connor; Jim Evans; Rowland Sharp; Matthew Gollock; Fenella R. Wood; James Rosindell; Charlie Bartlett; Brett J. Garner; et al. (Journal of Fish Biology, 2022)
The angelshark ( Squatina squatina ) has the northernmost range of any angel shark species, but there is limited information on its distribution, habitat use and ecology at higher latitudes. To address this, Angel Shark Project: Wales gathered 2231 S. squatina records and 142 anecdotal resources from fishers, coastal communities and archives. These spanned the coastal waters of Wales and the central Irish Sea and were dated from 1812 to 2020, with 97.62% of records within 11.1 km (6 nm) of the coast. Commercial, recreational and charter boat fishers provided the majority of S. squatina records (97.18%), with significantly more sightings from three decades (1970s, 1980s and 1990s) and in the months of September, June, August and July (in descending order). The coastal area between Bardsey Island and Strumble Head had the most S. squatina records ( n = 1279), with notable concentrations also found in Carmarthen Bay, Conwy Bay and the Outer Severn Estuary. Species distribution models (SDM) identified four environmental variables that had significant influence on S. squatina distribution, depth, chlorophyll‐a concentration, sea surface temperature (SST) and salinity, and these varied between the quarters (Q) of the year. SDM model outputs predicted a larger congruous area of suitable habitat in Q3 (3176 km 2 ) compared to Q2 (2051 km 2 ), with suitability along the three glacial moraines (Sarn Badrig, Sarn‐y‐Bwch and Sarn Cynfelyn) strongly presented. Comparison of modelled environmental variables at the location of S. squatina records for each Q identified reductions in depth and salinity, and increases in chlorophyll‐a and SST when comparing Q2 or Q3 with Q1 or Q4. This shift may suggest S. squatina are making seasonal movements to shallow coastal waters in Q2 and Q3. This is supported by 23 anecdotal resources and may be driven by reproductive behaviour, as there were 85 records of S. squatina individuals ≤60 cm in the dataset, inferred as recently born or juvenile life‐history stages. The results have helped fill significant evidence gaps identified in the Wales Angelshark Action Plan and immediate next research steps are suggested.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

DISSOLUTION PROFILE SIMILARITY ANALYSES—STATISTICAL PRINCIPLES, METHODS AND CONSIDERATIONS - Thomas Hoffelder; David Leblond; Leslie Van Alstine; Dorys Argelia Diaz; Sandra Suarez-Sharp; Krista Witkowski; Stan Altan; James Reynolds; Zachary Bergeron; Kevin Lief; Yanbing Zheng; Andreas Abend (The AAPS Journal, 2022)

JA:2021-31. Does the Use of a Nasal Lavage Intervention Improve Pulmonary Function for Dairy Workers? - James Seidel; Grant Erlandson; Julia D. Labadie; Sheryl Magzamen; Julia Sharp; Ken Jones; Matthew Nonnenmann; Stephen J. Reynolds; Joshua W. Schaeffer (Journal of Agromedicine, 2020)

Reference points for predators will progress ecosystem‐based management of fisheries - Simeon L. Hill; Jefferson Hinke; Sophie Bertrand; Lowell Fritz; Robert W. Furness; James N. Ianelli; Matthew Murphy; Ricardo Oliveros‐Ramos; Lorien Pichegru; Rowland Sharp; Richard A. Stillman; Peter J. Wright; et al. (Fish and Fisheries, 2020)
Ecosystem‐based management of fisheries aims to allow sustainable use of fished stocks while keeping impacts upon ecosystems within safe ecological limits. Both the FAO Code of Conduct for Responsible Fisheries and the Aichi Biodiversity Targets promote these aims. We evaluate implementation of ecosystem‐based management in six case‐study fisheries in which potential indirect impacts upon bird or mammal predators of fished stocks are well publicized and well studied. In particular, we consider the components needed to enable management strategies to respond to information from predator monitoring. Although such information is available in all case‐studies, only one has a reference point defining safe ecological limits for predators and none has a method to adjust fishing activities in response to estimates of the state of the predator population. Reference points for predators have been developed outside the fisheries management context, but adoption by fisheries managers is hindered a lack of clarity about management objectives and uncertainty about how fishing affects predator dynamics. This also hinders the development of adjustment methods because these generally require information on the state of ecosystem variables relative to reference points. Nonetheless, most of the case‐studies include precautionary measures to limit impacts on predators. These measures are not used tactically and therefore risk excessive restrictions on sustainable use. Adoption of predator reference points to inform tactical adjustment of precautionary measures would be an appropriate next step towards ecosystem‐based management.

Unique combinations of coral host and algal symbiont genotypes reflect intraspecific variation in heat stress responses among colonies of the reef-building coral, Montipora digitata - Javid Kavousi; Vianney Denis; Victoria Sharp; James Davis Reimer; Takashi Nakamura; John Everett Parkinson (Marine Biology, 2020)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Critical Review on the Public Health Impact of Norovirus Contamination in Shellfish and the Environment: A UK Perspective - Francis Hassard; Jasmine H. Sharp; Helen Taft; Lewis LeVay; John P. Harris; James E. McDonald; Karen Tuson; James Wilson; David L. Jones; Shelagh K. Malham (Food and Environmental Virology, 2017)

Plate-based diversity subset screening generation 2: an improved paradigm for high-throughput screening of large compound files - Andrew S. Bell; Joseph Bradley; Jeremy R. Everett; Jens Loesel; David McLoughlin; James Mills; Marie-Claire Peakman; Robert E. Sharp; Christine Williams; Hongyao Zhu (Molecular Diversity, 2016)

Plate-based diversity subset screening: an efficient paradigm for high throughput screening of a large screening file - Andrew S. Bell; Joseph Bradley; Jeremy R. Everett; Michelle Knight; Jens Loesel; John Mathias; David McLoughlin; James Mills; Robert E. Sharp; Christine Williams; Terence P. Wood (Molecular Diversity, 2013)

Ecological Implications of Changes in the Arctic Cryosphere - Warwick F. Vincent; Terry V. Callaghan; Dorthe Dahl-Jensen; Margareta Johansson; Kit M. Kovacs; Christine Michel; Terry Prowse; James D. Reist; Martin Sharp (Ambio, 2011)

Air-sea Coupling During the Tropical Cyclones in the Indian Ocean: A Case Study Using Satellite Observations - Bulusu Subrahmanyam; V. S. N. Murty; Ryan. J. Sharp; James. J. O’Brien (Pure and Applied Geophysics, 2005)

Risk Management for Petroleum Reservoir Production: A Simulation-Based Study of Prediction - James Glimm; Shuling Hou; Hongjoong Kim; Yoon-ha Lee; David H. Sharp; Kenny Ye; Qisu Zou (Computational Geosciences, 2001)

Does erythrocyte infusion improve 3.2-km run performance at high altitude? - Kent B. Pandolf; Andrew J. Young; Michael N. Sawka; James L. Kenney; Mark W. Sharp; Randy R. Cote; Beau J. Freund; C. Robert Valeri (European Journal of Applied Physiology, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

Self-administration in rats allowed unlimited access to nicotine - James D. Valentine; Jonathan S. Hokanson; Shannon G. Matta; B. M. Sharp (Psychopharmacology, 1997)